Identification of a Novel Heterozygous Missense Mutation in the CACNA1F Gene in a Chinese Family with Retinitis Pigmentosa by Next Generation Sequencing. (17th May 2015) - Zhou, Qi; Cheng, Jingliang; Yang, Weichan; Tania, Mousumi; Wang, Hui; Khan, Md. Asaduzzaman; Duan, Chengxia; Zhu, Li; Chen, Rui; Lv, Hongbin; Fu, Junjiang
Abstract : Background. Retinitis pigmentosa (RP) is an inherited retinal degenerative disease, which is clinically and genetically heterogeneous, and the inheritance pattern is complex. In this study, we have intended to study the possible association of certain genes with X-linked RP (XLRP) in a Chinese family. Methods. A Chinese family with RP was recruited, and a total of seven individuals were enrolled in this genetic study. Genomic DNA was isolated from peripheral leukocytes, and used for the next generation sequencing (NGS). Results. The affected individual presented the clinical signs of XLRP. A heterozygous missense mutation (c.1555C>T, p.R519W) was identified by NGS in exon 13 of the CACNA1F gene on X chromosome, and was confirmed by Sanger sequencing. It showed perfect cosegregation with the disease in the family. The mutation at this position in the CACNA1F gene of RP was found novel by database searching. Conclusion. By using NGS, we have found a novel heterozygous missense mutation (c.1555C>T, p.R519W) in CACNA1F gene, which is probably associated with XLRP. The findings might provide new insights into the cause and diagnosis of RP, and have implications for genetic counseling and clinical management in this family.